2020
DOI: 10.1016/j.ijpe.2020.107762
|View full text |Cite
|
Sign up to set email alerts
|

Operational resilience, disruption, and efficiency: Conceptual and empirical analyses

Abstract: A B S T R A C TThis research develops the notion of operational resilience and investigates its relationship with operational efficiency under differing conditions of operational disruption. Operational resilience is conceptualized as a multi-dimensional construct, consisting of two theoretically distinct components (i.e., disruption absorption and recoverability), which are argued to have unique effects on operational efficiency under varying operational disruption conditions. The study's hypotheses are empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 53 publications
2
96
0
Order By: Relevance
“…The Latin America and Caribbean are potential workshop to replace Asia for North America and Europe. The certitude and operative constancy must be noticed when building resilience and flexibility approaches, which positively improve operational efficiency ( Ivanov and Dolgui, 2019 , Essuman et al, 2020 ). However, the lack of information and uncertainty, and the absence of the external knowledge are navigating their activities and unsustain their existence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Latin America and Caribbean are potential workshop to replace Asia for North America and Europe. The certitude and operative constancy must be noticed when building resilience and flexibility approaches, which positively improve operational efficiency ( Ivanov and Dolgui, 2019 , Essuman et al, 2020 ). However, the lack of information and uncertainty, and the absence of the external knowledge are navigating their activities and unsustain their existence.…”
Section: Discussionmentioning
confidence: 99%
“… Alamerew and Brissaud (2020) explored the system dynamics using TBL aspects from a close-loop SC to grants a complex systemic model of reverse logistics to recover end-of-life products based on cost, revenue, regulatory, and strategic decisions; and proposed that researchers, practitioners, policy makers need to improve their knowledge sharing among the main CE pillars and the strengthen the interaction among numerous decision factors. Essuman et al (2020) developed the operational resilience notion and investigated its effects on operational efficiency under different operational disruptive situations and found both disruption absorption and recoverability have positive relationship to operational efficiency. Fattahi et al (2020) provides a stochastic optimization of disruption drives on SC network design to measures the expected SC's surplus cost with new resilience metric that quickly and effectively forms the SC back to its original or even more desirable state after the disruption and during its recovery phase.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decades, an enormous array of methods and tools has been developed, which can be applied to decision-making support under uncertainty ( Silbermayr and Minner, 2014 ; Demirel et al, 2019 ; Li and Zobel, 2020 ). We refer to comprehensive surveys on these operational and disruption risks ( Klibi et al, 2010 ; Snyder et al, 2016 ; Shen and Li, 2017 ; Hosseini et al, 2019a , b ; Ghadge et al, 2019 ; Yu et al, 2019 ; Essuman et al, 2020 ). Similar literature on epidemics and humanitarian disasters in the context of SCs and logistics presents a body of promising methods and outcomes ( Altay and Green, 2006 ; Dasaklis et al, 2012 ; Gupta et al, 2016 ; Dubey et al, 2019b ; Fosso Wamba, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the supply chain management field, resilience is described as "the adaptive capability of the supply chain to prepare for unexpected events, respond to disruptions, and recover from them by maintaining continuity of operations at the desired level of connectedness and control over structure and function" (Ponomarov and Holcomb 2009, p. 131). Essuman et al (2020) have considered a number of studies to discuss both operational and supply chain resilience and found that different researchers consider resilience from different perspectives; for example, at focal firm level, at supply chain level, supply network, and supply system.…”
Section: Introductionmentioning
confidence: 99%